Enacting Multiliteracy in Young Learners’ English Classrooms: A Case Study of Primary Teachers - Ramadhani Uswatun Khasanah; Ragil Dian Purnama Putri (JURNAL INOVASI DAN MANAJEMEN PENDIDIKAN, 2025)
Multiliteracy focuses on multimodal communication and linguistic and cultural diversity. It is increasingly relevant in 21st-century primary education. In Indonesian elementary English classrooms, multiliteracy opens space for more engaging learning but also introduces pedagogical and infrastructural constraints. This study explores how primary teachers implement multiliteracy-oriented practices in English lessons and identifies the challenges that arise during classroom application. Employing a qualitative case study, data were gathered through interviews, classroom observations, and document analysis involving six teachers. The results show that teachers integrated various multimodal resources, such as images, songs, videos, and mobile devices. The teachers also applied interactive strategies, including role-play, games, and group discussion. Furthermore, the teachers modified teaching materials to accommodate students’ proficiency levels. Nonetheless, limited student vocabulary, inadequate technological support, and teachers’ restricted English competence emerged as key barriers. Despite these constraints, students responded positively to multimodal and interactive activities, displaying strong enthusiasm and engagement in the learning process.